267 Pseudoprogression patterns: Analysis from 2 independent phase-2 studies with immunotherapy for recurrent cervical cancer. (9th November 2020) - O'Malley, David; Feliu, Waldo Ortuzar; Ray-Coquard, Isabelle; O'Neal, Michael; Alexandre, Jerome; Cole, Julie; Ludwig, Robert; Nallewar, Madhavi; Buell, Jennifer; Kaleta, Remigiusz; Wijatyk, Anna; Borisovskaya, Victoria
Abstract : Background: The phenomenon of pseudoprogression (PsP) may appear with cancer immunotherapy. The underlying etiology is not fully elucidated, tumor flare is the suspected mechanism of early pseudoprogression that may resolve gradually while continuing treatment. Further, immunotherapy-induced sarcoidosis may mimic PsP. Here we present examples of 3 observed patterns of PsP in cervical cancer (CC) patients treated with balstilimab (BAL; anti-PD-1), alone or in combination with zalifrelimab (ZAL; anti-CTLA-4). Methods: The evaluated patients received either BAL 3 mg/kg every 2 weeks alone (NCT03104699 ) or in combination with ZAL dosed at 1 mg/kg every 6 weeks (NCT03495882 ). PsP was defined as radiologic disease progression per RECIST1.1 followed by a significant reduction of measurable baseline lesions, disappearance of the non-measurable lesions, or no further progression for at least two tumor assessments after initial progressive disease (PD) by Independent Evaluation Review Committee (IERC). PsP was divided into 3 categories – early (before or at week 12 of treatment), delayed (after week 12) and serial (at least 2 PsP occurrences). Results: Overall, 313 patients with post-chemotherapy recurrent CC with baseline measureable disease were treated with either BAL (n=160) or in combination with ZAL (n=143). Early PsP was observed in 7 patients treated with BAL and 8 with BAL/ZAL while 5 patients experienced delayed PsP (BAL (n=1); ZAL(n=4)). Serial PsP was observed in 1 patient (BAL only) and another (n=1) BAL treated experienced showed PsP (new Mediastinal lesions) present in 2 consecutive CT scan evaluations before disappearance – hence were classified as PD even by iRECIST. Immune-related sarcoidosis was confirmed histologically in 2 patients following confirmation by mediastinal lymph node biopsy. PsPs were accompanied with clear clinical benefit of disease improvement and weight stabilization, improvement in performance status, and decreased painPsP BAL (N=160)) BAL/ZAL (N=143)Early 7 (4%) 8 (6%)Delayed 1 (<1%) 4 (3%) Serial 1 (<1%) -Total 09 (6%) 12 (8.3%). Conclusions: This is the first report of PsP in CC population. PsP-confounded IERC evaluation of tumor response was seen in some CC patients treated with BAL or combination of BAL and ZAL. The differentiation of PD and PsP has important consequences for disease assessment in clinical trials and disease management and outcomes. Further efforts to elucidate the underlying mechanisms and clearly define the characteristics of PsP are crucial for better treatment management of affected patients. Standard response evaluation systems including iRECIST may need further refinement to recognize the importance of PsP. Trial Registration: NCT03104699 and NCT03495882 Ethics Approval: C-700-01 : The WIRB Study # is 1173375 and the site IRB approval # is 20170314. and for C-550-01: ICON Cancer Center in South Brisbane, Queensland, Australia.- IRB approval # is 2017-10-766.